The mechanic [videorecording (DVD)] - Statham, Jason, 1967-; Foster, Ben, 1980-; Sutherland, Donald, 1935-2024; Anden, Mini; Goldwyn, Tony (Sony Pictures Home Entertainment, 2011)
"Arthur Bishop ... is a 'mechanic' - an elite assassin with a unique talent for cleanly eliminating targets-- and Bishop is the best in the business. But when his mentor and close friend Harry ... is murdered, Bishop is intent on exacting revenge. His mission grows complicated when Harry's son Steve ... approaches him with the same vengeful goal. But while in pursuit of their ultimate mark, deceptions threaten to surface and those hired to fix problems become problems themselves"--Container.